The educational function of agrotourism using the example of Siedlce region - Kowalski, Ryszard; Stoczkowska, Renata; Obrębska, Maria; Marciszewska, Urszula (Studia Ecologiae et Bioethicae, 2007)
The aim of this research was to evaluate the educational offers of agrotourist farms in the Siedlce region, the research was conducted on the grounds of interviews with the farm owners and information provided by Mazowiecki Ośrodek Doradztwa Rolnieczego “Mazowsze - agrotourism 2005/2006”. The results confirm the assumption that agrotourist farms carry on an informal environmental education for their customers, but there are possibilities for improvement of this educational activity, the farm owners need appropriate preparation to fulfill the role of guides and teachers.